Analisis Kinerja Keuangan Pemerintah Desa Bedingin Kecamatan Sambit Kabupaten Ponorogo Periode 2020-2022 - Dilla Ika Mariani; Arif Hartono; Ika Farida Ulfah (Trending: Jurnal Manajemen dan Ekonomi, 2024)
Measuring village government financial performance is very important to ensure that village financial management is appropriate. This research aims to analyze the effectiveness, efficiency, growth and contribution to the financial performance of the Bedingin Village Government, Sambit District, Ponorogo Regency. This research method uses a qualitative descriptive approach. The research results show that the average level of effectiveness of Village Original Income and Transfer Income from 2020-2022 is included in the effective criteria. The average level of efficiency of Village Original Income expenditure and Transfer Income expenditure from 2020-2022 is included in the less efficient criteria. The average growth rate of Village Original Income and Transfer Income from 2020-2022 grew very low. The average contribution of Transfer Income to Village Original Income from 2020-2022 is included in the very good criteria.